Actitudes parentales hacia la ESI en secundaria: Ecuador versus contextos internacionales. - Vera Castro, Verónica Jacqueline (My University, 2025)
Comprehensive Sex Education (CSE) in secondary education is a scientific intervention that promotes healthy development in adolescents, but faces barriers due to parental perceptions. The objective was to analyze parental perceptions and attitudes toward CSE program implementation in secondary educational centers, considering cultural gaps between Ecuador and international contexts. A systematic review methodology following PRISMA was used, analyzing 74 studies published between 2010-2025. Results show that parental perceptions in Ecuador are influenced by cultural, social, and religious factors, generating significant gaps compared to international contexts, with greater resistance in traditional contexts and greater acceptance in societies with consolidated inclusive educational policies.
La Educación Sexual Integral (ESI) en secundaria es una intervención científica que promueve el desarrollo saludable en adolescentes, pero enfrenta barreras por las percepciones parentales. El objetivo fue analizar las percepciones y actitudes parentales hacia la implementación de programas de ESI en centros educativos secundarios, considerando las brechas culturales entre Ecuador y contextos internacionales. Se utilizó metodología de revisión sistemática siguiendo PRISMA, analizando 74 estudios publicados entre 2010-2025. Los resultados evidencian que las percepciones parentales en Ecuador están influenciadas por factores culturales, sociales y religiosos, generando brechas significativas respecto a contextos internacionales, con mayor resistencia en contextos tradicionales y mayor aceptación en sociedades con políticas educativas inclusivas consolidadas.aaaaaaaaa
Keywords: ACTITUDES PARENTALES; CREENCIAS PARENTALES; EDUCACIÓN SEXUAL; EDUCACIÓN SEXUAL INTEGRAL